Conceptual framework. Planning inclusive cities and human settlements. Entry points for international development cooperation. - Wissenbach, Lars (universi - Universitätsverl. Siegen, 2019)
Recent developments in the field of international cooperation call for renewed attention to the role of local governance in development and emphasize the role of local governments and local communities for processes of inclusion and public well-being. The UN Convention on the Rights of Persons with Disabilities obliges States Parties to make local development processes inclusive. The 2030 Agenda on Sustainable Development, the UN HABITAT III New Urban Agenda and further global policy frameworks reaffirm the role of the local level for sustainable development and emphasize the need to foster accessible public infrastructure in cities and municipalities. Today, local governments across the globe exert a decisive influence over the living conditions and quality of life of a nation’s citizens, including persons with disabilities. This raises the need for an in-depth discussion on the role of organizing the immediate physical and social environment of cities and municipalities with regard to the elimination of barriers and the provision of opportunities for participation and living a self-determined life. This concept paper was produced in cooperation with the Deutsche Gesellschaft für Internationale Zusammenarbeit (GIZ) Global Project ‘Inclusion of Persons with Disabilities’, on behalf of the German Federal Ministry for Economic Cooperation and Development (BMZ). It provides a strategic perspective and a basic conceptual framework for disability-inclusive local development. It aims to equip policy makers and practitioners in the fields of international cooperation and local development with a conceptual approach and practical entry points for disability mainstreaming in cities and municipalities.
Keywords: Stadtentwicklung; Stadtplanung; Inklusion; Barrierefreiheit; Planungsbeteiligung; Partizipation; Nachhaltige Stadtentwicklung; Lokale Agenda; Internationale Zusammenarbeit